INTRAPERITONEAL AEROSOL CHEMOTHERAPY UNDER PRESSURE (IACUP) – AN INNOVATIVE METHOD OF TREATMENT OF PATIENTS WITH PERITONEAL CARCINOMATOSIS - A. D. Kaprin; V. M. Khomyakov; A. B. Ryabov; L. V. Bolotina; A. V. Ivanov; A. B. Utkina; V. V. Cheremisov; I. V. Kolobaev; A. V. Chaika; D. D. Sobolev; L. A. Koroleva (Исследования и практика в медицине, 2016)
Widespread peritoneal carcinomatosis in gastric cancer, in fact, is the end-stage of the disease. The survival median of patients is no more than 3–6 months. Development of various methods of intraperitoneal chemotherapy can improve the prognosis of this category of patients.Objective. To evaluate the efficacy and safety of intraperitoneal aerosol chemotherapy under pressure (IACUP) in patients with gastric cancer with peritoneal carcinomatosis.Materials and methods. The treatment Protocol consisted of a laparotomy or laparoscopy for the staging of the tumor process, 3–4 courses of systemic chemotherapy scheme XELOX followed by conducting at least 3 sessions of intraperitoneal aerosol chemotherapy under pressure (IACUP) with an interval of 6 weeks on the background of chemotherapy. In the case of progression the patient was excluded from the study. Currently, the study included 27 patients with disseminated gastric cancer who underwent 46 procedures of IACUP. There were 8 men and 19 women. The average age of patients was 50.6 years.Results. In the framework of the safety assessment of IACUP there were 3 cases of adverse effects. Two patients (7,4%) noted nausea for the first 2 days after running the session of IACUP. In one patient the iatrogenic perforation of the diaphragm during biopsy of the peritoneum with the development of carbonetworks occurred. The survival median was 11 months. One-year survival rate (by KaplanMeier) was 50.7%. 14 patients are alive and continue to participate in the study during the first year of observation.Conclusion. Intraperitoneal aerosol chemotherapy under pressure (IACUP) is a simple, minimally invasive and safe method for the palliative treatment of patients with disseminated carcinomatosis of gastric cancer. We developed the treatment Protocol that allows us to achieve one-year survival of more than half of patients.